2021
DOI: 10.1371/journal.pone.0254140
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of male circumcision in four culturally non-circumcising counties in western Kenya after 10 years of program implementation from 2008 to 2019

Abstract: Introduction Kenya started implementing voluntary medical male circumcision (VMMC) for HIV prevention in 2008 and adopted the use of decision makers program planning tool version 2 (DMPPT2) in 2016, to model the impact of circumcisions performed annually on the population prevalence of male circumcision (MC) in the subsequent years. Results of initial DMPPT2 modeling included implausible MC prevalence estimates, of up to 100%, for age bands whose sustained high uptake of VMMC pointed to unmet needs. Therefore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…In Kisumu, among men aged 15–49, three consecutive surveys [ 26 ] showed a male circumcision prevalence of 31.9 (95% CI 28.4–35.5) in 2009, 48.8% (95% CI 46.2–51.4) in 2011 and 59.7% (95% CI 57.0–62.3) in 2013. The remaining two studies reported a male circumcision prevalence of 50.6% (95% CI 49.3–51.9) in 2014 to 71.2% (95% CI 69.7–72.7) in 2019 in Siaya, Kisumu, Homa Bay and Migori Counties among men younger than 35 years [ 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…In Kisumu, among men aged 15–49, three consecutive surveys [ 26 ] showed a male circumcision prevalence of 31.9 (95% CI 28.4–35.5) in 2009, 48.8% (95% CI 46.2–51.4) in 2011 and 59.7% (95% CI 57.0–62.3) in 2013. The remaining two studies reported a male circumcision prevalence of 50.6% (95% CI 49.3–51.9) in 2014 to 71.2% (95% CI 69.7–72.7) in 2019 in Siaya, Kisumu, Homa Bay and Migori Counties among men younger than 35 years [ 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…The odds of STI were 2-fold higher among circumcised vs. uncircumcised males, and over 50% of male participants were circumcised. The study area includes traditionally non-circumcising communities, 50 which since 2008, have been targeted by Kenya's National HIV Program for aggressive programmatic scale-up of VMMC to reduce HIV transmission risk among heterosexual men. [51][52][53] The protective effects of male circumcision may be partially offset by increased sexual risk behaviour as a result of lower perception of HIV infection risk after circumcision.…”
Section: Discussionmentioning
confidence: 99%
“…These reductions in recent HIV infections are likely due to multiple factors, including the scale-up of biomedical prevention interventions, including voluntary medical male circumcision (VMMC) in traditionally noncircumcising communities, 26 expansion of ART eligibility in 2012 and 2016, and rapid increases in HIV testing, diagnosis, and treatment leading to reduced population HIV viral load and subsequent transmission. Although disparities in educational attainment and household wealth were not consistently linked to greater individual risk of recent HIV infection as shown in Rakai, Uganda, 27 societal changes, such as increasing household wealth and increasing educational attainment, as well as behavioral changes may have contributed to overall reductions in HIV incidence.…”
Section: Discussionmentioning
confidence: 99%